The Contribution Of Islamic Banks To The Achievement Of Social Responsibility – Case Study Al Baraka Banking Group – - أوصيف لخضر; فرحاتي لويزة (khazzartech الاقتصاد الصناعي, 2021)
Through this study, we seek to highlight the importance of Islamic institutions and banks’ role in establishing the principles of social responsibility and their contribution and assistance in developing societies. Although the State is a guiding and a driving force in all economic, social development fields and processes it cannot carry out all developmental roles alone and meet all the requirements and needs of its people. So, it was necessary to integrate organizations, companies, institutions, and banks to contribute to the development processes by carrying out their social responsibilities in the communities in which they operate, and allocating axes from its activity’s programs for cooperation and solidarity with government agencies. Thus, becoming a partner and a fundamental supporter in this area.